2001
DOI: 10.1109/77.919847
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of rapidly-heated/quenched and transformed Nb/sub 3/Al multifilamentary superconducting wires

Abstract: Microstructures of rapidly-heated/quenched and transformed Nb& multifilamentary wires were studied by using transmission electron microscopy. Nb/AI composite wires are fabricated by a jelly-roll process. The Nb/AI composite filaments changed into Nb-AI supersaturated bcc solid solution with the rapidly-heating/quenching. The Nb-AI bcc phases consists of many crystal grains with diameters of 2-4 pm, surrounded with large-angle grain boundaries. Some spherical voids, about 0.1 micron in diameter, were also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…The as-quenched untransformed Nb(Al) in the 1.275 mm wire has a mean grain Feret diameter of 3 m (similar to the 2-4 m reported by Kikuchi et al [4] from TEM analysis. Processed to Cu-clad tape the grain size is reduced and the aspect ratio of the grains increases from 1.53 to 1.92.…”
Section: A Microstructural Quantificationsupporting
confidence: 52%
See 3 more Smart Citations
“…The as-quenched untransformed Nb(Al) in the 1.275 mm wire has a mean grain Feret diameter of 3 m (similar to the 2-4 m reported by Kikuchi et al [4] from TEM analysis. Processed to Cu-clad tape the grain size is reduced and the aspect ratio of the grains increases from 1.53 to 1.92.…”
Section: A Microstructural Quantificationsupporting
confidence: 52%
“…Two successful modifications to the basic RHQT technique specifically address the stacking fault issue: In the double rapidly-heating/quenching, DRHQ, technique the standard RHQT process is followed but instead of a conventional low temperature ( 1000 C) transformation heat treatment a second RQH process produces the A15 phase and this is followed by a long range ordering heat treatment at 800 C for 12 hrs (7). The for these stacking fault free strands has been measured at 18.4 K, which suggests very good stoichiometry; furthermore a critical current density of 135 A/mm was obtained at 25 T [4]. A disadvantage of this technique is that the brittle A15 phase is formed during high temperature processing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that when a RHQ treatment is applied to Nb and Al raw materials, a solid solution of NbAl y with a bcc structure is formed [6][7][8][9][10][11][12]. Upon further heat treatment, this undergoes an A15 phase transformation to form Nb 3 Al.…”
Section: Introductionmentioning
confidence: 97%